Globalization and the muslim world - Abdul Razak, Mohd Abbas (Research and Management Centre, IIUM, 2011)
History indicates that before the coming of modern globalization, the Muslims had their own version of globalization. During the Muslim era of globalization which coincides with the Golden Age of the Muslims, the West benefited immensely from the scholastic works produced by Muslim scientists and scholars. Modern globalization which started during the era of Western colonization of the East has now gone to every nook and cranny of the world. The usage of internet and other modern electronic media directly or indirectly has speeded up the process of transporting modern globalization to the world community. Modern globalization has brought about radical change in aims of education; it has marginalized local culture and language; it has caused brain drain everywhere in the world. Muslims, it seems, are perceiving globalization as identical to re-colonization. This paper intends to explore and investigate how modern globalization heralded by the west is different from Muslim globalization in the past.